2015
DOI: 10.1016/j.jneumeth.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

AICHA: An atlas of intrinsic connectivity of homotopic areas

Abstract: AICHA is ideally suited for intrinsic/effective connectivity analyses, as well as for investigating brain hemispheric specialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
221
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(225 citation statements)
references
References 70 publications
(91 reference statements)
3
221
1
Order By: Relevance
“…While this is expected for the Broca area of the inferior frontal gyrus, regions such as the dorsal part of the frontal eye fields (FEF) and the ventral region of the ventrolateral pre-frontal cortex (VLPFC) are usually activated bilaterally (Joliot et al, 2015), whereas here we find the activation in these regions strongly biased to the left hemisphere. This lateralization has been associated with the cognitive control of memory access (Badre & Wagner, 2007).…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…While this is expected for the Broca area of the inferior frontal gyrus, regions such as the dorsal part of the frontal eye fields (FEF) and the ventral region of the ventrolateral pre-frontal cortex (VLPFC) are usually activated bilaterally (Joliot et al, 2015), whereas here we find the activation in these regions strongly biased to the left hemisphere. This lateralization has been associated with the cognitive control of memory access (Badre & Wagner, 2007).…”
Section: Resultscontrasting
confidence: 75%
“…This lateralized activation is unusual because attentional and oculomotor activation of these regions is usually bilateral (Joliot et al, 2015). Such activation may represent an extension of the language processing area of the ventral premotor area in this blind individual without the need for oculomotor planning, or it may represent instead a preserved latent form of eye-hand mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Both nuclei are directly adjacent to the ventral part of the ventral lateral posterior nucleus (VLpv) which (in Hirai & Jones nomenclature) corresponds to the VIM (in Walker nomenclature) or Vimi (in Hassler nomenclature; Macchi and Jones, 1997). Thalamic parcellations based on anatomical connectivity (Behrens et al, 2003), showed the DBS target in premotor and primary motor zones of the thalamus, while parcellations based on functional connectivity showed it between motor and sensory (Zhang et al, 2008) or in thal-5 zone (Joliot et al, 2015). Finally, the VIM DBS target could be related to histological MNI-based resources such as the BigBrain dataset (Amunts et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In this approach areas were defined based on the assumption that similar connectivity profiles could be found within a region (Johansen-Berg et al 2004; Klein et al 2007). More recent hypotheses emphasize parcellations based on functional connectivity, e.g., a definition of the putative areas SMA and pre-SMA using resting state fMRI (Kim et al 2010; Joliot et al 2015). Another approach identified areas SMA and pre-SMA in a data-driven fashion based on their individual co-activation patterns (Eickhoff et al 2011).…”
Section: Introductionmentioning
confidence: 99%